2019
DOI: 10.1093/jn/nxz044
|View full text |Cite
|
Sign up to set email alerts
|

Pinto Beans (Phaseolus vulgaris L.) Lower Non-HDL Cholesterol in Hamsters Fed a Diet Rich in Saturated Fat and Act on Genes Involved in Cholesterol Homeostasis

Abstract: Background Pinto beans contain multiple active agents such as polyphenols, flavonoids, and saponins, and have been shown to lower cholesterol, but the mechanisms involved in this effect have not been explored. Objective This study was to investigate the changes in cholesterol metabolism in response to whole pinto beans (wPB) and their hulls (hPB) supplemented into a diet rich in saturated fat and the molecular mechanisms pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Yeap et al [ 60 ] found that feeding diets containing fermented mung beans to hypercholesterolemic mice significantly reduced their serum levels of triglycerides, cholesterol, and LDL cholesterol. Similar cholesterol-lowering effects of pinto beans have been observed using a hamster model [ 61 ]. We observed that mice fed the bean diets had higher diet consumption and body weight gain ( Figure S2 in the Supplementary Material ), which was also inconsistent with previous findings of the weight-lowering effects of another common bean (white kidney bean) in obese mice [ 33 ].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Yeap et al [ 60 ] found that feeding diets containing fermented mung beans to hypercholesterolemic mice significantly reduced their serum levels of triglycerides, cholesterol, and LDL cholesterol. Similar cholesterol-lowering effects of pinto beans have been observed using a hamster model [ 61 ]. We observed that mice fed the bean diets had higher diet consumption and body weight gain ( Figure S2 in the Supplementary Material ), which was also inconsistent with previous findings of the weight-lowering effects of another common bean (white kidney bean) in obese mice [ 33 ].…”
Section: Discussionsupporting
confidence: 71%
“…Neither of the bean diets affected plasma lipid profile compared with the HF diet ( Figure 1 ). This was unexpected, since many animal studies suggest a hypolipidemic effect of bean foods [ 32 , 59 , 60 , 61 ]. Diet supplementation with dietary fiber from white kidney bean was reported to reduce total cholesterol in the serum of diabetic rats [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…123 A recent study also provides support for the role of pulse phytochemicals with their examination of whole pinto beans and a supplement of pinto bean hulls (markedly higher in total phenolic content) in a saturated fat-rich diet on cholesterol metabolism and molecular mechanisms in a hamster model. 124 Results showed that both the whole pinto beans and pinto bean hulls significantly decreased non-HDL cholesterol compared with control (by 31.9% and 53.6%, respectively) and also caused hepatic mechanistic changes, including lower liver cholesterol, higher fecal cholesterol, and higher expressions of cholesterol metabolic enzymes. 124 The glucose-lowering effects of pulses, like their lipid-lowering effects, have also been attributed to numerous pulse components including dietary fiber, resistant starch, and phytochemicals.…”
Section: Mechanisms Of Action Of How Pulses Can Improve Circulating Lmentioning
confidence: 91%
“…124 Results showed that both the whole pinto beans and pinto bean hulls significantly decreased non-HDL cholesterol compared with control (by 31.9% and 53.6%, respectively) and also caused hepatic mechanistic changes, including lower liver cholesterol, higher fecal cholesterol, and higher expressions of cholesterol metabolic enzymes. 124 The glucose-lowering effects of pulses, like their lipid-lowering effects, have also been attributed to numerous pulse components including dietary fiber, resistant starch, and phytochemicals. For example, pulse fiber has been shown to reduce postprandial glycemic response by delaying carbohydrate digestion and glucose absorption.…”
Section: Mechanisms Of Action Of How Pulses Can Improve Circulating Lmentioning
confidence: 91%
“…Corn has a protein content of 9.3–15.8%, mainly composed of zeins and globulins ( 26 29 ). Common beans present a protein content of 19.1–28.3%, including albumins, phaseolins, and glutelins ( 29 33 ). Pumpkin seeds are rich in protein with 21.3–37.7%, mainly constituted of globulins, glutelins, and albumins ( 12 , 34 37 ).…”
Section: Macronutrientsmentioning
confidence: 99%